2014
DOI: 10.1352/1944-7558-119.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and the Behavior Problems of Young Children With an Intellectual Disability: Concurrent and Longitudinal Relationships in a Population-Based Study

Abstract: We examined parenting behaviors, and their association with concurrent and later child behavior problems. Children with an intellectual disability (ID) were identified from a UK birth cohort (N  =  516 at age 5). Compared to parents of children without an ID, parents of children with an ID used discipline less frequently, but reported a more negative relationship with their child. Among children with an ID, discipline, and home atmosphere had no long-term association with behavior problems, whereas relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 46 publications
4
68
1
Order By: Relevance
“…A substantial amount of research has demonstrated that children with developmental disability exhibit increased levels of behavioral problems compared to their nondisabled peers (e.g., de Ruiter, Dekker, Verhulst, & Koot, 2007) and that they are three times more likely to be rated in the clinical range compared to typically developing children (e.g., Totsika, Hastings, Vagenas, & Emerson, 2014). It has been shown that increased levels of behavior problems emerge at least by the preschool years (e.g., Baker, Blacher, Crnic, Edelbrock, & Low, 2003) and can persist across middle childhood into adolescence and even into adulthood (e.g., Einfeld et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of research has demonstrated that children with developmental disability exhibit increased levels of behavioral problems compared to their nondisabled peers (e.g., de Ruiter, Dekker, Verhulst, & Koot, 2007) and that they are three times more likely to be rated in the clinical range compared to typically developing children (e.g., Totsika, Hastings, Vagenas, & Emerson, 2014). It has been shown that increased levels of behavior problems emerge at least by the preschool years (e.g., Baker, Blacher, Crnic, Edelbrock, & Low, 2003) and can persist across middle childhood into adolescence and even into adulthood (e.g., Einfeld et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, similar gains were experienced for parenting style, despite evidence of a differential parenting approach by parents with a child with disability (less discipline use but more negative relationship; Totsika et al, 2014). Similar gains were evident for parental mental well-being, an area that has received substantial research attention in families of children with disabilities.…”
Section: Discussionmentioning
confidence: 74%
“…First, while having access to a large, longitudinal dataset is an asset, datasets (such as the MCS) that are designed for multiple purposes commonly utilise abbreviated forms of measures such as the abbreviated scales of cognitive functioning (rather than complete IQ tests) used in the MCS. While it is common practice in such instances to use the available data to derive a proxy measure of IQ (cf., Schoon et al 2005;Jones & Schoon 2008;Parsons 2014;Totsika et al 2014), the association between the proxy and full measure is unknown. Second, while the overall sample was relatively large, it was of insufficient size to examine the extent to which our results may have varied by severity of ID.…”
Section: Discussionmentioning
confidence: 99%
“…For ages 5 and 7, we extracted the first component ('g') from a principal component analysis of all agestandardised sub-scale/test scores (cf., Schoon et al 2005;Jones & Schoon 2008;Parsons 2014;Totsika et al 2014). The first component accounted for 63% of score variance at age 7 and 55% of score variance at age 5.…”
Section: Identification Of Children With Intellectual Disabilitiesmentioning
confidence: 99%